2022
DOI: 10.3390/ijms231911006
|View full text |Cite
|
Sign up to set email alerts
|

Proof-of-Principle Study Suggesting Potential Anti-Inflammatory Activity of Butyrate and Propionate in Periodontal Cells

Abstract: Short-chain fatty acids (SCFAs) are potent immune modulators present in the gingival crevicular fluid. It is therefore likely that SCFAs exert a role in periodontal health and disease. To better understand how SCFAs can module inflammation, we screened acetic acid, propionic acid, and butyric acid for their potential ability to lower the inflammatory response of macrophages, gingival fibroblasts, and oral epithelial cells in vitro. To this end, RAW 264.7 and primary macrophages were exposed to LPSs from Porphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
(107 reference statements)
2
4
0
Order By: Relevance
“…Moreover, lower SCFAs concentrations are found in circulation compared to the gut, with acetic acid, butyric acid, and propionic acid concentrations ranging 19–160, 1–13, and 1–12 µmol/L, respectively [ 45 , 46 ]. Similar to most studies, the human THP-1 cells were exposed to mM-range concentrations of SCFAs in the current study, with consistent findings that SCFAs treatment decreased the LPS-induced production of inflammatory factors [ 47 , 48 ]. Notably, Qi Hui et al revealed the anti-inflammatory effect of 20 μmol/L butyrate on LPS-induced human peripheral blood mononuclear cells [ 49 ].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, lower SCFAs concentrations are found in circulation compared to the gut, with acetic acid, butyric acid, and propionic acid concentrations ranging 19–160, 1–13, and 1–12 µmol/L, respectively [ 45 , 46 ]. Similar to most studies, the human THP-1 cells were exposed to mM-range concentrations of SCFAs in the current study, with consistent findings that SCFAs treatment decreased the LPS-induced production of inflammatory factors [ 47 , 48 ]. Notably, Qi Hui et al revealed the anti-inflammatory effect of 20 μmol/L butyrate on LPS-induced human peripheral blood mononuclear cells [ 49 ].…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were observed in macrophages, where propionate and butyrate but not acetate strongly inhibited inflammatory response 23 . Interestingly, butyrate and propionate also possess anti-inflammatory properties in other cell types such as iPSC-derived intestinal epithelia and periodontal tissue 24 , 25 . Butyrate was found to be the SCFA with the most consistent effects on NK cell metabolism and activation receptors at the concentrations used (1 mM, 2.5 mM and 5 mM).…”
Section: Discussionmentioning
confidence: 99%
“…[ 52 ] Butyrate was effective in reducing the lipopolysaccharide (LPS)‐induced expression of IL6 and chemokine (C‐X‐C motif) ligand 2 (CXCL2) in the macrophages. [ 53 ] Butyrate exerts anti‐inflammatory role by inhibiting the nuclear factor kappa‐light‐chain‐enhancer of activated B cells (NF‐kappa B) signaling pathway. [ 54 ] The mechanisms by which intestinal microbiota play beneficial or detrimental roles in immune‐mediated back pain remain to be further investigated.…”
Section: Discussionmentioning
confidence: 99%